Impact of Audio Visual Media Utilization Toward Early Childhood Speaking Proficiency - Kaderia; Nurhayati; Amrullah; Zakiyatul Imamah (Universitas Negeri Semarang, 2025)
Speaking proficiency plays a vital role in early childhood as a foundation for communication and literacy development. However, many children still face difficulties in expressing their thoughts verbally during classroom interactions. This study was conducted to examine the impact of audio-visual media on improving speaking skills among Group B kindergarten students at RA DDI Pasangkayu. A quantitative approach was employed using a one-group pre-test–post-test design involving 24 children. Data were collected through observation of children’s speaking performance before and after learning with audio-visual media. The results showed a significant improvement in speaking proficiency, with an increase in the “Very Well Developed” category from 0% to 43.05%. The paired t-test analysis obtained a t-value of 14.454, which exceeded the t-table value of 2.06866 (p < 0.05), indicating a statistically significant effect. These findings confirm that the integration of audio-visual media effectively enhances children’s speaking abilities. This study provides recent empirical evidence supporting the effectiveness of audio-visual learning in early childhood education. The findings contribute to enriching learning practices by encouraging teachers to adopt engaging and interactive media to support children’s language and communication development.